Faktor Resiko Umur >35 Tahun dan Anemia Ringan : (Studi Kasus Terhadap Ny. A di Puskesmas Pangkah Kabupaten Tegal) - Elsa Olivia Ashara; Adevia Maulidya Chikmah; Umriyati Umriyati (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Based on data obtained from the Pangkah Health Center, Tegal Regency in 2022, the number of maternal mortality rates (MMR) was 2 cases caused by amniotic fluid bleeding and embolism, whereas in 2023 it was zero or non-existent (Recap of PWS KIA data from Pangkah Community Health Center 2023). The aim of this study was to examine obstetric cases with high risk aged >35 years and mild anemia. This research uses a case study approach. The research subject was pregnant mother Mrs. A is 36 years old with high risk, aged >35 years and mild anemia. Data was taken from October to November 2023. Data was taken using interviews, observation and documentation, the results during pregnancy, the subjects accepted to have their Hb checked because at visit 2 the Hb was low and the results were the same as at visit 3-4 the Hb was high and normal. Pregnant women aged >35 years are still often found or are more at risk because the mother's health has declined, as a result pregnant women at that age have a high probability of preeclampsia, bleeding, preterm labor and others. Suggestion: if a similar case is found, collaboration with a doctor is necessary. during pregnancy until postpartum, apart from that it is necessary to involve the family, especially the child during pregnancy and after the baby is born.